Role of Promotional Strategies in Customer Retention at a Music Studio in Rizal, Philippines - Jesus Briones; Cyrus Emmanuel S Cabog; Aileen R Eugenio; Karen B Bobiles; Kirsten Charisse C Chua; Efren Jr R Abergos (Journal of Social Entrepreneurship Theory and Practice, 2025)
Promotional strategies serve a vital role in enhancing customer satisfaction and loyalty. In relation to customer retention, these strategies are essential for fostering long-term engagement. This study examines the role of promotional strategies in customer retention at a music studio in Rizal, Philippines. Using a descriptive–correlational research design, data were collected through a researcher-developed structured questionnaire where all items were measured using a four-point Likert scale administered to 158 qualified customers. The Cronbach’s alpha test was used for reliability analysis, and data were analyzed using descriptive statistics and simple linear regression analysis. The findings revealed that the studio’s digital promotion and value proposition were highly effective, as the studio maintains a strong online presence and communicates service value clearly. In customer retention, findings showed that clients exhibit strong loyalty and community engagement, driven by positive experiences, trust, and a sense of belonging. Moreover, several challenges were identified, including accessibility issues, inconsistent communication, and limited follow-up with former clients. The study provides several proposed strategies to strengthen digital promotion and value proposition to gain customer loyalty and community engagement, which can offer valuable insights for other music studios to improve their promotional strategies and draw plans for customer retention.